A Study on Parameters Influencing Business Sustainability for Tribal Women Farmer Group’s Running Micro, Small, and Medium Enterprises (MSMEs) in India - Selvaraj, Aravazhi (Digital Repository of Theses, 2026)
Socio-economic empowerment of tribal women to involve them in socio-economically productive activities and to provide them with steady income–generating avenues is still an issue in India. The Micro, Small, and Medium Enterprises (MSMEs) have been a major source of the rural tribal women farmer groups’ socio-economic development, as a result, they have become the agents of their own and the community’s economic growth. This study is to find out the factors that have a significant influence on the sustainability of the tribal women farmer groups’ MSMEs in Telangana, India, through environmental, social, governance, and financial parameters. The study employed a mixed-method research design that combined quantitative and qualitative components. Information directly from the source was gathered through interviews after a predefined questionnaire was prepared. The interviews were conducted among 100 tribal women entrepreneurs, community leaders, and government officials. The study, after collecting secondary data from various government publications, policy papers, and relevant pieces of literature, proceeded to analyse the quantitative data using SPSS (Statistical Package for the Social Sciences), which included Spearman's Rank Correlation and Ordinal Regression. Qualitative insights were also analysed thematically during this period, and they were instrumental in the validation and the reliability of the statistics. According to the data, the indigenous women MSMEs ' survival was credited to various factors that were not only complex but also closely interrelated. The most significant factor for the business's continuance was the management and operation styles, which, along with others, featured the leadership, innovation, and resource management as indicated in the correlation analysis (ρ = 0.673, p < 0.01). According to the research, the environment was identified as the primary source of the problems which had the biggest impact on the longevity of the business (Nagelkerke R² = 0.728, p < 0.01). The social factors of the common impact, cultural sustainability, and social well-being were also individually significant contributors to the total model (Nagelkerke R² = 0.781, p < 0.01). Moreover, the indicators linked to governance, such as policy compliance, transparency, and institutional support, were very powerful in leading to a sustainable enterprise stage change (Nagelkerke R² = 0.686, p < 0.01One of the main factors that made businesses sustainable was financial literacy, which in fact, had a substantial positive influence (Nagelkerke R² = 0.420, p = 0.000). On the other hand, if credit access was considered as the only factor, it would not have resulted in statistically significant findings. The study sees tribal women-run MSMEs as an intricate environmental care, social relations, good governance, and community economic empowerment, mainly, a complex system. The revival and sustainability of the business ventures of the tribal women in India have been mostly reliant on the availability of a strong legal structure, wide-ranging financial literacy programs, and the institutional reforms that are making user-friendly services easier. Keywords: Tribal Women Entrepreneurs; Micro, Small and Medium Enterprises (MSMEs); Business Sustainability; Environmental Factors; Social Empowerment; Governance Frameworks; Telangana; Sustainable Entrepreneurship; Rural Development; Inclusive Growth